PENGEMBANGAN VIDEO INTERAKTIF TERHADAP PENDIDIKAN SEKS ANAK USIA DINI DITINJAU DARI SEGI MORAL ANAK DI TK NUR IKHLAS TARAM - Rini Aulia Fitri; Delfi Eliza (Jurnal Educhild : Pendidikan dan Sosial, 2022)
This study aims to develop an interactive video on early childhood sex education in terms of morals. The method used is Research and Development (R&D) with a 4-D model. This research was conducted at Nur Ikhlas Taram Kindergarten. In this study, the stages of validation, practicality and effectiveness were carried out. The results of the validity test obtained an average of 80.22% while the practicality test of the teacher's response reached 90.18℅ and 93.43℅ for children's learning observations, testing the effectiveness of learning activities reached 92.41℅ and the effectiveness of children's learning outcomes 84.35℅. Based on these results, interactive video media for early childhood sex education in terms of morals that were developed can be used and practically applied in Kindergarten.